Incidence of Dengue in the Highland District Swat, Pakistan: A Major Shift in the Geographical Prevalence of the Disease: Incidence of Dengue in District Swat, Khyber Pakhtunkhwa-Pakistan - Gul, Rehman; Tabassum, Iffat; Ullah, Ihsan; Rahman, Fazlur (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Dengue disease has been known as a major public health problem in recent years throughout the world including Pakistan. During 2013 out-break in Pakistan it has shown wider spread to areas which were never endemic to it: more importantly spreading in higher latitude and altitude. To understand its expansion, particularly in the northern mountainous belt we conducted a study in Swat District of Pakistan. Aim of this study was to investigate the factors of this unexpected spread and epidemiology of dengue disease in newly hit area, District Swat. A sample of 180 households was selected for questionnaire survey from the hospital patients’ records. Among total population of the selected households around quarter of people endured from disease during last spell. Male were the highest victims particularly between ages of 16-45 years, as they were the most mobile people carrying the virus from other urban centers of Pakistan such as Karachi, Lahore and Peshawar. The result further specified that increased movement into the district from historically endemic region was the igniting factor.